The Case of a 44-Year-Old Survivor of Unrepaired Tetralogy of Fallot, Right Aortic Arch and Abdominal Aortopulmonary Collateral Vessels - Roxana Ciltea; Alina Ioana Nicula; Mircea Bajdechi; Alexandru Scafa-Udriste; Roxana Rimbas; Gheorghe Iana; Dragos Vinereanu (Medicina, 2022)
The most common congenital cyanotic heart disease is described in the literature as the Tetralogy of Fallot. This abnormality is characterized by the presence of ventricular septal defect (VSD), obstruction of the right ventricular (RV) outflow tract, right ventricular hypertrophy, and overriding aorta. In patients with pulmonary atresia with ventricular septal defect (PA/VSD), major aortopulmonary collateral arteries (MAPCA) are common; however, although some of them do not have PA/VSD, they do have other particular anatomical variants. The case we are presenting in this article is a rare mild symptomatic adult noncorrected TOF, with preserved RV function, right aortic arch, and MAPCAs (“classic” thoracic MAPCAs but also abdominal MAPCAs). The anatomy of a complex congenital defect is well illustrated by cardiac magnetic resonance (CMR) and computer tomography angiography (CTA), and these imaging techniques are mostly used to understand the relative clinical “silence” TOF. Imaging scans thus play a key role in the evaluation of these patients, being very important to know the indications and limitations of each method, but also to learn to combine them with each other depending on the clinical picture of the patient’s presentation. Additionally, the close collaboration between clinicians and imagers is essential for a correct, complete and detailed preoperative evaluation, being subsequently essential for cardiovascular surgeons, the whole team thus deciding the best therapeutic management.